Life Satisfaction Among Individuals with Physical Disabilities in Saudi Arabia: The Impact of Physical Activity, Self-Perceived Health and Fitness, and Sociodemographic Features - Majed M. Alhumaid; Mohamed A. Said; Selina Khoo (Medicina, 2024)
Background and Objectives: Life satisfaction (LS) is a key aspect of mental well-being, particularly for individuals with physical disabilities (IWPDs).This study examined LS levels among IWPDs in Saudi Arabia, focusing on the effects of three independent variables: (i) sociodemographic factors, (ii) self-reported health and fitness, and (iii) self-assessed physical activity (PA). Materials and Methods: Data was collected from 271 participants using validated questionnaires. Two models analyzed the effects of the independent variables on LS: the first model included the overall level of PA, while the second examined its individual components. Results: The results indicated that females reported a higher LS than males (p = 0.011). Participants with a university degree demonstrated a significantly greater LS compared to those who did not disclose their educational status (Exp(β) = 1.104). Poor health and inactivity were linked to a lower LS, while age correlated positively with LS (odds ratio = 1.012). Additional factors, including marital status, income, education level, and mobility assistance usage, significantly impacted LS. Interestingly, PA exhibited no direct statistical effect on LS. Conclusions: These findings highlight the importance of equitable access to education, regular PA, support for married couples, and preventive healthcare. Special attention to young people, particularly boys, is recommended to improve LS outcomes among IWPDs in Saudi Arabia.